Postoperative Treatment of Distal Radius Fractures Using Sensorimotor Rehabilitation - Wollstein, Ronit; Harel, Hani; Lavi, Idit; Allon, Raviv; Michael, Dafna (Journal of Wrist Surgery, 2019)
Background Sensorimotor and specifically proprioception sense has been used in rehabilitation to treat neurological and joint injuries. These feedback loops are not well understood or implemented in wrist treatment. We observed a temporary sensorimotor loss, following distal radius fractures (DRF) that should be addressed postsurgery.Purpose The purpose of this prospective therapeutic study was to compare the outcomes of patients following surgery for DRF treated using a sensorimotor treatment protocol with those patients treated according to the postoperative standard of care.Patients and Methods Patients following surgery for DRF sent for hand therapy were eligible for the study. Both the evaluation and treatment protocols included a comprehensive sensorimotor panel. Patients were randomized into standard and standard plus sensorimotor postoperative therapy and were evaluated a few days following surgery, at 6 weeks, and 3 months postsurgery.Results Sixty patients following surgery were randomized into the two treatment regimens. The initial evaluation was similar for both groups and both demonstrated significant sensorimotor deficits, following surgery for DRF. There was documented sensorimotor and functional improvement in both groups with treatment. The clinical results were better in the group treated with the sensorimotor-proprioception protocol mostly in the wrist; however, not all of the differences were significant.Conclusion Patients after surgery for DRF demonstrate significant sensorimotor deficits which may improve faster when utilizing a comprehensive sensorimotor treatment protocol. However, we did not demonstrate efficacy of the protocol in treating proprioceptive deficits. Further study should include refinement of functional outcome evaluation, studying of the treatment protocol, and establishment of sensorimotor therapeutic guidelines for other conditions.Level of Evidence This is a level II, therapeutic study.
Keywords: distal radius fracture; postoperative; proprioception; rehabilitation; sensorimotor therapy